Effect of Calcium Hydroxide on the Push-out Bond Strength of Endodontic Biomaterials in Simulated Furcation Perforations - Ghasemi, Negin; Frough Reyhani, Mohammad; Salem Milani, Amin; Mokhtari, Hadi; Khoshmanzar, Faezeh (Iranian Endodontic Journal, 2016)
Introduction: The aim of this in vitro study was to evaluate the effect of calcium hydroxide (CH) on push-out bond strength of white mineral trioxide aggregate (WMTA) and calcium-enriched mixture (CEM) cement in simulated furcation perforations. Methods and Materials: Furcation perforations, measuring 1.3 mm in diameter and 2 mm in height, were created in 80 human mandibular first molars. The teeth were then divided into 4 groups (n=20). In groups 1 and 3 CH was placed in the perforation for one week, before placement of WMTA and CEM. In groups 2 and 4 perforations were repaired without placement of CH. In groups 1 and 2 the perforation sites were repaired with WMTA and CEM cement was used in groups 3 and 4. After 7 days, the push-out test was carried out using a universal testing machine. Data were analyzed with two-way ANOVA. The level of significance was set at 0.05. Results: The maximum and minimum bond strength values were recorded in the WMTA/CH (13.08±1.8 MPa) and CEM cement groups (8.03±0.98 MPa), respectively. There were significant differences in resistance to dislodgement between the WMTA/CH and other groups (P<0.05). Conclusion: Placement of CH before placement of WMTA in furcation perforation improves the push-out bond strength of this material. Keywords: Calcium-Enriched Mixture; Calcium Hydroxide; Furcation Perforation; Mineral Trioxide Aggregate; Push-Out